2021
DOI: 10.1055/a-1552-3239
|View full text |Cite
|
Sign up to set email alerts
|

Antireflux mucosectomy (ARMS) and antireflux mucosal ablation (ARMA) for gastroesophageal reflux disease: a systematic review and meta-analysis

Abstract: Background and study aims Antireflux mucosectomy (ARMS) and antireflux mucosal ablation (ARMA) are new endoscopic procedures for patients with gastroesophageal reflux disease (GERD). We conducted a meta-analysis to systematically assess the feasibility, clinical success, and safety of these procedures. Patients and methods We searched Embase, PubMed, and Cochrane Central from inception to October 2020. Overlapping reports, animal studies, and case reports were excluded. Our primary outcomes were clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…A strength of this systematic review is the thorough inclusion of up-to-date articles, with critical appraisal and analysis. Although another recent meta-analysis compared ARMS and ARMA, 35 we excluded studies with small sample sizes to reduce bias, and we also explored factors such as postoperative GEJ competency and risk factors for treatment failure in detail. Furthermore, the current analysis was comprehensive as we also included ARBL due to its similarity to ARMS in concept and technique, except that no resection is performed.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of this systematic review is the thorough inclusion of up-to-date articles, with critical appraisal and analysis. Although another recent meta-analysis compared ARMS and ARMA, 35 we excluded studies with small sample sizes to reduce bias, and we also explored factors such as postoperative GEJ competency and risk factors for treatment failure in detail. Furthermore, the current analysis was comprehensive as we also included ARBL due to its similarity to ARMS in concept and technique, except that no resection is performed.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 single arm pilot study found significant improvement in DeMeester scores and GERD-HRQL scores among 12 patients 62. A 2021 meta-analysis of non-randomised studies revealed similar levels of efficacy between ARMS and ARMA with acceptable safety profile 63…”
Section: Other Techniquesmentioning
confidence: 99%
“… 62 A 2021 meta-analysis of non-randomised studies revealed similar levels of efficacy between ARMS and ARMA with acceptable safety profile. 63 …”
Section: Other Techniquesmentioning
confidence: 99%
“…73 Antireflux mucosectomy and antireflux mucosal ablation have gained particular interest because they do not require add-on devices and are not technically difficult to perform. 74 Currently, no long-term RCTs are available to add this procedure to the armamentarium for GERD treatment.…”
Section: Endoscopic Mucosal Resectionmentioning
confidence: 99%